PERAN PEMERINTAH DESA TERHADAP KELOMPOK TANI MATUARI DI DESA TOUNELET SATU KECAMATAN SONDER - Tambuwun, Monica; Olfie, Benu L. S.; Maweikere, Audrey Julia Maria (Sam Ratulangi University, 2022)
This study aims to determine the role of the village government towards. Matuari Farmer Group in Tounelet Satu Village, Sonder District. This research was carried out in November 2019 to January 2020 starting from preparation, data collection to preparing research reports. The data collection method in this study used primary data and secondary data. Primary data was obtained directly from the source through surveys and interviews using a list of questions to all members of the Matuari Farmer Group, while secondary data was obtained from the village office of Tounelet Satu, Sonder District. The results showed the role of the village government in the Matuari farming group in tounelet village, sonder'scamtan showed well. Judging from the role of the government in advancing the group, namely: 1). The Role of the Village Government in Advancing the Matuari Peasant Group, 2). Government Assistance Provided to Matuari Farmers Group, 3). Relationship Between The Village Government and Members of the Matuari Peasant Kelomok, 4). Trust Between The Village Government and the Peasant Group.